ASEAN's Response to the COVID-19 Pandemic in the Political and Security Sector - Jati, Abisatya Kurnia; Farizka, Afifah Amalia; Nasywa, Hanani; Meliana, Willies (Universitas Sebelas Maret, 2020)
The end of 2019 to continue the beginning of 2020, the world has been shocked by a new type of virus that at that time could not be identified and occurred for the first time in China. With the development of its transmission, the COVID-19 virus or corona virus is classified as a virus that spreads rapidly. High transmission of course affects areas bordering or with high mobility charts, such as South Korea, Japan and Italy. Responding to the coronavirus case, the World Health Organization (WHO) has taken many actions. One of them is holding a meeting of virologists and disease management through various media, directly or indirectly, to identify the possibility of the corona virus occurring and being contagious. This is a challenge that must be resolved by many countries. Empathy and solidarity between countries are considered as the first steps to reduce the number of infections. In this regard, regional international organizations such as ASEAN have an important role to play in resolving this problem. The purpose of this journal article is made to see the response given by international organizations in the ASEAN region, in the political and security sector during the coronavirus pandemic.